A tonsillectomy increased the risk of chronic rhinosinusitis among children: A three-year follow-up study. (December 2016) - Chung, Shiu-Dong; Lin, Herng-Ching; Wu, Chuan-Song; Kao, Li-Ting; Hung, Shih-Han
Abstract: Objectives: The study aimed to estimate the risk of developing chronic rhinosinusitis (CRS) among children who had undergone a tonsillectomy by utilizing a cohort study based on a population-based database. Methods: Data for this retrospective cohort study were sourced from the Taiwan "Longitudinal Health Insurance Database 2000". We included 202 children who had undergone a tonsillectomy as the study group and 2020 sex- and age-matched children as the comparison group. We used stratified Cox proportional hazard regressions to calculate the hazard ratio (HR) and its corresponding 95% confidence interval (CI) for CRS during the 3-year follow-up period. Results: Of 2222 sampled children, the incidence rate of CRS during the 3-year follow-up period was 3.2 (95% CI = 2.0–4.8) 1000 person-years; 18.2 (95% CI = 9.1–32.5) per 1000 person-years and 1.7 (95% CI = 0.8–3.0) per 1000 person-years for the study and comparison group, respectively. The stratified Cox proportional analysis showed that the adjusted hazard ratio for CRS during the 3-year follow-up period was 8.28 (95% CI = 3.24–21.16) for children who had undergone a tonsillectomy than comparison patients. Conclusions: We demonstrated that the risk of developing CRS is significantly increased among children who have undergone a tonsillectomy.